2011
DOI: 10.3727/096368910x557236
|View full text |Cite
|
Sign up to set email alerts
|

Neural Differentiation of Brain-Derived Neurotrophic Factor-Expressing Human Umbilical Cord Blood-Derived Mesenchymal Stem Cells in Culture via TrkB-Mediated ERK and β-Catenin Phosphorylation and following Transplantation into the Developing Brain

Abstract: The ability of mesenchymal stem cells (MSCs) to differentiate into neural cells makes them potential replacement therapeutic candidates in neurological diseases. Presently, overexpression of brain-derived neurotrophic factor (BDNF), which is crucial in the regulation of neural progenitor cell differentiation and maturation during development, was sufficient to convert the mesodermal cell fate of human umbilical cord bloodderived MSCs (hUCB-MSCs) into a neuronal fate in culture, in the absence of specialized in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 64 publications
0
28
0
Order By: Relevance
“…As described previously for MSCs or adult NSCs overexpressing untagged BDNF (Lim et al, 2011;Ma et al, 2012), or as revealed by application of BDNF to EBs (Kang et al, 2001) or to NSCs (Silva et al, 2009), neuronal differentiation of our BDNF-GFPoverexpressing ESCs was strongly enhanced (Figs 4,5). Given that this enhancement was critically dependent on the extracellular availability of BDNF (see inhibition by TrkB-Fc receptor bodies; Fig.…”
Section: Enhanced Neuronal Differentiation Of Bdnf-gfp Escsmentioning
confidence: 94%
See 2 more Smart Citations
“…As described previously for MSCs or adult NSCs overexpressing untagged BDNF (Lim et al, 2011;Ma et al, 2012), or as revealed by application of BDNF to EBs (Kang et al, 2001) or to NSCs (Silva et al, 2009), neuronal differentiation of our BDNF-GFPoverexpressing ESCs was strongly enhanced (Figs 4,5). Given that this enhancement was critically dependent on the extracellular availability of BDNF (see inhibition by TrkB-Fc receptor bodies; Fig.…”
Section: Enhanced Neuronal Differentiation Of Bdnf-gfp Escsmentioning
confidence: 94%
“…To put the present level of overexpression into context, relatively high levels of virusmediated BDNF expression in bone marrow stromal cells, MSCs and adult NSCs have been previously shown to exert beneficial effects, for example after grafting into lesioned tissue (see e.g. Lim et al, 2011;Ma et al, 2012;Makar et al, 2008;Makar et al, 2009). Furthermore, modest endogenous levels of BDNF protein in mesenchymal and neural stem cells (Chekhonin et al, 2011;Li et al, 2006;Mauri et al, 2012) have also been shown to be beneficial on co-cultured neurons (Mauri et al, 2012).…”
Section: Expression Level Of Bdnf-gfp In Escsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lim et al transplanted BDNF-expressing hUCB-MSCs into the lateral ventricle of healthy mouse pups on first postnatal day (101). These genetically modified hUCB-MSCs were found to be able to survive, migrate, and differentiate into periventricular astrocytes and olfactory bulb neurons, and performed better than non-engineered hUCB-MSCs under the same conditions.…”
Section: Effect Of Huc-mscs In Animal Models Of Perinatal Brain Injurymentioning
confidence: 99%
“…Few years later, after genetically modifying UCB-MSCs through transfection with a BDNF-expressing plasmid, they showed the expression of βIII-tubulin, NeuN, GFAP and myelin basic protein (MBP) in differentiated cells, associated with an up-regulated phosphorylation level of TrkB, Raf-1 and ERKs [77].…”
Section: Neurotrophic Factors and Downstream Signaling Pathwaysmentioning
confidence: 99%